Tari Satriyeng Bencingah - Novitasari, Ni Luh Ria; Padmini, Tjok Istri Putra; Suandewi, Gusti Ayu Ketut (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
The Satriyeng Bencingah dance is a new dance creation that elevates the spirit of struggle carried out by Ida I Dewa Ayu Den Bencingah and his female troops using Belida weapons to fight the enemy who attacked the Bangli kingdom in 801 AD. Satriyeng means knight and hate is the name of Ida I Dewa Ayu Den Bencingah. Satriyeng Bencingah's dance creations were inspired by witnessing a sacred heirloom, namely Belida during the Panca Wali Krama ceremony in 2019 at the Kahen Bangli Temple. Belida is a weaving tool that functions as a unifier between one yarn and another.The process of creating a dance created by Satriyeng Bencingah uses the Alma M Hawkin creation method using three stages, namely exploration, improvisation, and forming. The process of creating this creative dance work uses the theory of imagination and aesthetic theory so that the work is able to convey the message desired by the stylist, namely that women are not weak, able to struggle and do not judge things from the outside.The presentation of the work of Satriyeng Bencingah dance is performed by 7 female dancers in a structured manner which is divided into flashback sections describing Belida being functioned as a loom, part one describes the majesty of Ida I Dewa Ayu Den Bencingah, part two describes inner turmoil and part three describes the spirit of struggle and victory with accompanied by Gamelan Gong Kebyar and gerong vocals.Keywords: Satriyeng Bencingah Creative Dance, Belida, Ida I Dewa Ayu Den Bencingah.